Loss of ARID1A leads to a cold tumor phenotype via suppression of IFNγ signaling - Pamela M. Watson; Chelsea A. DeVaux; Kevin W. Freeman (Scientific Reports)
Abstract The collapse of inflammatory signaling that recruits cytotoxic immune cells to the tumor microenvironment contributes to the immunologically cold tumor phenotype in neuroblastoma (NB) and is a barrier to NB immunotherapy. Multiple studies have reported that MYCN amplification, a trait of high-risk NB, correlates with a loss of inflammatory signaling; but MYCN also correlates with 1p36 deletions in NB where the SWI/SNF chromatin remodeling complex subunit ARID1A (1p36.11) is located. ARID1A is known to support inflammatory signaling in adult cancers but its role in NB inflammatory signaling is unexplored. We find MYCN overexpression causes a stronger inflammatory response to interferon-gamma (IFNγ). ARID1A knockdown causes a weaker inflammatory response and reduces IFNγ induced gene signatures for the transcription factor interferon response factor 1 (IRF1). We found ARID1A is a functional interactor of IRF1 by co-immunoprecipitation studies, and ARID1A silencing causes loss of activating chromatin marks at the IRF1 target gene CXCL10. We model that IRF1 uses ARID1A containing SWI/SNF to promote CXCL10 in response to IFNγ. Our work clarifies that the loss of ARID1A, which tightly associates with MYCN amplification, causes reduced inflammatory signaling. This work finds that ARID1A is a critical regulator of inflammatory signaling in NB and provides rationale for testing immune therapies in MYCN amplified NB that are effective in adult ARID1A mutated cancers.